Odpowiedź :
Odpowiedź:
c)
5/4 (1-r) - 1/4 = 3/4(r-4) + 3
5/4 - 5/4 r - 1/4 = 3/4r - 3 + 3
1 - 5/4r = 3/4r / *4
4 - 5r = 3r
-5r - 3r = -4
-8r = -4 / :(-8)
r = 4/8
r = 1/2
h)
0,1(r-10) - 0,6r = 1,5r - 4
0,1r - 1 - 0,6r = 1,5r - 4
-0,5r - 1,5r = -4 + 1
-2r = -3 /:(-2)
r = 3/2
r = jeden i jedna druga (1 1/2)
Szczegółowe wyjaśnienie:
Odpowiedź:
Szczegółowe wyjaśnienie:
B
c)
(8-x)/2 + (5+x)/4 = 12(1 -x/48)
(8-x)/2 + (5+x)/4 = 12 -x/4) / *4
16 - 2x + 5 + x = 48 - x
-2x + x + x = 48 - 21
0 ≠ 27
równanie sprzeczne, nie posiada rozwiązań !
h)
(4-x+2)/7 = (8x-3+2x)/(-10) / * (-70)
-10*(6-x) = 7*(10x-3)
-60 + 10x = 70x - 21
60x = -39
x = -39/60 = - 13/20